Performance of optimum and suboptimum combining at the antenna array of a W-CDMA system. - Dell'Anna, M. (IEEE Journal on selected areas in communications)
The performance of an array of antennas combined with a RAKE receiver at the base station of a wideband code division multiple access system with quaternary phase shift keying modulation is investigated for single-user reception. This receiver structure is also known as a multidimensional RAKE receiver. Expressions for the interference correlation matrix are derived, and subsequently, an analysis of the error probability is provided. With regard to antenna weights, the optimum combining linear receiver, which takes into account the spatial distribution of all the users in the system, is compared with the suboptimum combining receiver (SOC), which exploits knowledge of the desired user array vector only. It is shown how the two receivers, ideal in the sense that perfect channel estimation is assumed, achieve very similar performances under realistic conditions. Consequently, the investigated pilot assisted combining receiver, which estimates the channel based on limited overhead, calculates weights according to the SOC strategy by a very simple algorithm